2020
DOI: 10.1101/2020.05.28.121145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interleukin-6 trans-signaling is a candidate mechanism to drive progression of human DCCs during periods of clinical latency

Abstract: 28Although thousands of breast cancer cells disseminate and home to bone marrow until 29 primary surgery, usually less than a handful will succeed in establishing manifest 30 metastases months to years later. To identify signals that support survival or outgrowth 31 in patients, we profiled rare bone marrow-derived disseminated cancer cells (DCCs) 32 long before manifestation of metastasis and identified IL6/PI3K-signaling as candidate 33 pathway for DCC activation. Surprisingly, and similar to mammary epithel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 87 publications
2
2
0
Order By: Relevance
“…3b-e). This is in line with a recent study showing IL6 pathway activation in patient-derived early disseminated BCC in bone marrow (30).…”
Section: Discussionsupporting
confidence: 93%
“…3b-e). This is in line with a recent study showing IL6 pathway activation in patient-derived early disseminated BCC in bone marrow (30).…”
Section: Discussionsupporting
confidence: 93%
“…By using single-cell transcriptomic and pathway analysis, we found that IL-6 and G-CSF engagement in non-canonical signaling via the ERK/MAPK pathway, involved in fibrosis and wound healing response (52,53), to be crucial in cancer cells outgrowth (Fig. 3), instead of the canonical JAK/STAT signaling pathway involved in inflammatory response as shown by previous studies (17,51). The gene signatures identified in the chemotherapy group agreed with previous studies on dormant-emergent cancer and chemoresistance (18,42).…”
Section: Discussionsupporting
confidence: 64%
“…Clinical data from several studies show that taxane therapy increases serum IL-6 and G-CSF levels in patients (45,46) and that higher levels of serum IL-6 is a prognostic marker for early breast cancer recurrence in patients receiving systemic therapy (47,48). Additionally, IL-6 and G-CSF have been widely implicated in cancer invasiveness (49,50) and recent studies have also shown a role of trans-IL-6 activating JAK/STAT signaling in dormancy awakening (51). However, the mechanistic role of IL-6 and G-CSF in inducing dormancy escape has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, inhibiting TAK1 disrupts MM-BMSC adhesion, inhibits osteoclast (OC) genesis, and may revive osteoblastic activity [4]. Melanie Werner-Klein et al determined that the IL-6/PI3K pathway plays a significant role in activating disseminated cancer cells (DCCs) despite their lack of membrane-bound IL-6 receptors, with IL-6 trans-signaling prompting a stem-like state in mammary epithelial cells through gp130 [34]. Further research by Matthew Ho and his team demonstrated that disabling Histone deacetylase 3 (HDAC3) via knock-out (KO), knock-down (KD), or pharmacological methods in BMSCs reduces myeloma cell proliferation, effectiveness confirmed in patient-derived myeloma cell cultures with BMSCs [35].…”
Section: The Immune and Metabolic Microenvironment In MMmentioning
confidence: 99%